"Making Mystics Out of Cheese": Flannery O'Connor's Grotesque Reimagination of Pride and Humility in A Prayer Journal and "The Lame Shall Enter First". Issue 5 (4th July 2019) - Taylor, Alex
ABSTRACT: This article explores the work of Flannery O'Connor as a unique twentieth century Catholic author, who understood the metaphysical and moral crisis of her day as confronting a pervasive nihilism which denied the existence of objective good and evil and any sense of transcendent, universal morality such as the Thomistic understanding of virtue and vice central to the Christian moral tradition. The author first examines A Prayer Journal (2013), which O'Connor wrote as a young MFA student, to explore her earliest use of grotesque aesthetics in her implicit reimagining of pride and humility as connected to true self-knowledge and knowledge of God. He then uses this moral framework to ground a literary reading of O'Connor's story "The Lame Shall Enter First" focused on the tragic pride of Sheppard, O'Connor's revelatory use of a satanic narrative voice, and the grotesque humility in the diabolic prophet character, the juvenile delinquent Rufus Johnson. The author seeks to cast light on questions related not only to literature, moral theology and moral philosophy but also on the intellectual history of the twentieth century Catholic recovery of metaphysics.